Sand im Getriebe. Aushandlungsprozesse um die Gewinnung mineralischer Rohstoffe aus konflikttheoretischer Perspektive nach Ralf Dahrendorf. - Weber, Florian; Kühne, Olaf; Jenal, Corinna; Aschenbrand, Erik; Artukovic, Ante (Springer VS, 2018)
Wie vielfältige gesellschaftliche Kontexte in Deutschland zeigen, kommt es zunehmend zu Protesten, mit denen Politik, Planung, Verbände und Unternehmen umgehen müssen. Es werden erstmalig Konflikte um die Gewinnung mineralischer Rohstoffe untersucht. Dazu werden verschiedene Analysebestandteile vor dem Hintergrund der Konflikttheorie Ralf Dahrendorfs ausgewertet und es wird danach gefragt, welche Regelungen denkbar erscheinen. Fazit: Konfliktregelungen als multidimensionale Herausforderungen.

The author examines the importance of regional cultural landscape for their residents using the approach of willingness to pay. She identifies that almost each resident of every region prefers water landscapes. Furthermore, landscape perception is often influenced by education and by the resident s relationship with nature. The impact of the relationship to the region differs between regions and resident groups. Regarding the involvement in or for the landscape, the results suggest that specific groups of residents are more willing to volunteer in and for regional landscapes than others. The analyses illustrate that the region is used the most to relax and the least for cultural purposes.
Keywords: Energie; Rohstoff; Gewinnung; Abbau; Methode; Befragung; Konfliktanalyse